The Friday Effect: Firm Lobbying, the Timing of Drug Safety Alerts, and Drug Side-Effects - Santaló, Juan; Barber, Benjamin; Diestre, Luis; Santaló, Juan (Informs, 2020)
Safety alerts are announcements made by health regulators warning patients and doctors about new drug-related sideeffects.However, not all safety alerts are equally effective. We provide evidence that the day of the week on which thesafety alerts are announced explains differences in safety alert impact. Specifically, we show that safety alerts announcedon Fridays are less broadly diffused – they are shared 34% less on social media, mentioned in 23-66% fewer news articles,and 12-51% less likely to receive any news coverage at all. As a consequence of this, we propose Friday alerts are lesseffective in reducing drug-related side-effects. We find that moving a Friday alert to any other weekday would reduceall drug-related side-effects by 9-12%, serious drug-related complications by 6-15%, and drug-related deaths by 22-36%.This problem is particularly important since Friday was the most frequent weekday for safety alert announcements from1999 to 2016. We show this greater prevalence of Friday alerts might not be random: firms who lobbied the FDA in thepast are 49-56% more likely to have safety alerts announced on Fridays.
Keywords: Healthcare;Safety alerts;FDA;Lobbying; Healthcare; Safety alerts; FDA; Lobbying; 53 Ciencias Económicas; ODS 3 - Salud y bienestar